2011
DOI: 10.1007/s00414-011-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for estimating wound age in contused rat skeletal muscle by quantitative real-time PCR

Abstract: Gene expression profiling by quantitative real-time PCR (RT-qPCR) is a valuable tool in forensic science for estimating the age of a wound. To accurately assess gene expression levels over time in injured tissue, the genes used as internal reference standards must be carefully validated for transcriptional stability. This study examined the transcriptional stability of nine potential reference genes (β-actin, GAPDH, RPL32, PGK1, SDHA, RPL13, HPRT, Tbp, and Ywhaz) in contused rat skeletal muscle by RT-qPCR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…RPL17 is a component of the 60S ribosomal subunit. Although several ribosomal proteins are variably expressed under disease conditions (Kobayashi et al 2006), they have been used as normalization genes (Sun et al 2012). In turbot (S. maximus), RPL17 is the most stable gene across tissue types before bacterial challenge (Dang and Sun 2011).…”
Section: Discussionmentioning
confidence: 99%
“…RPL17 is a component of the 60S ribosomal subunit. Although several ribosomal proteins are variably expressed under disease conditions (Kobayashi et al 2006), they have been used as normalization genes (Sun et al 2012). In turbot (S. maximus), RPL17 is the most stable gene across tissue types before bacterial challenge (Dang and Sun 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of transcription of reference genes was assayed with GeNorm system and total six reference genes were analyzed including Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), β -actin, 18 S rRNA gene, hypoxanthine phosphoribosyltransferase 1-like ( hprt1 ), epinephelus coioides ribosomal protein S29 ( rps29 ) and ribosomal protein L13 ( rpl13 ) [4749]. GeNorm analysis revealed that rpl13 was the most stable control gene in skeletal muscles (geNorm stability value M = 0.28).…”
Section: Methodsmentioning
confidence: 99%
“…Different normalization strategies have been employed to reduce variability in the qPCR amplification process including internal reference genes (RGs), normalization to initial amount of material and use of external control nucleotides [35]. Applying the use of internal RGs is the most accepted method since expression and amplification of both reference and target genes occur under the same conditions despite different sequences [2].…”
Section: Introductionmentioning
confidence: 99%